Mode of Proximal Tubule Damage: Differential Cause for the Release of TFF3? - Zwaini, Zinah; Alammari, Dalia; Byrne, Simon; Stover, Cordula (Frontiers in Immunology, 2016)
Proximal tubular epithelial cells are particularly sensitive to damage. In search of a biomarker, this study evaluated the potential of different cell activation models (hypoxia/replenishment and protein overload) to lead to a release of TFF3 (Trefoil factor 3). Surprisingly, we found disparity in the ability of the different stimuli to enhance the intracellular abundance of TFF3 and its release: While conditions of nutrient starvation and damage associated with replenishment lead to intracellular abundance of TFF3 in the absence of TFF3 release, stimulation with an excess amount of albumin did not yield accumulation of TFF3. By contrast, incubation of cells with a purified lambda light chain preparation from a patient with multiple myeloma provoked the presence of TFF3 in the cell supernatant. We therefore propose that elevations of TFF3 in renal disease might be more revelatory for the cause of restitution than previously thought.